B-cell responses in allergen immunotherapy. Issue 6 (December 2019) - Satitsuksanoa, Pattraporn; van de Veen, Willem; Akdis, Mübeccel
Abstract : Purpose of review: The establishment of long-term clinical tolerance in AIT requires the involvement of basophils, mast cells, allergen-specific regulatory T and B cells, downregulation of effector type 2 responses, and increase in production of specific IgG, particularly immunglobulin G4 (IgG4) antibodies. This review aims to provide an overview of the role of B cells in AIT, their mechanism of action, and their potential for improving AIT. Recent findings: In-depth research of B cells has paved the way for improved diagnosis and research on allergic diseases. B cells play a central role in allergy and allergen tolerance through the production of immunglobulin E (IgE)-blocking antibodies. However, an increasing body of evidence has emerged supporting a role for B cells in regulating immune responses that extends beyond the production of antibodies. Regulatory B cells play an important role in immunosuppression, mediated by secretion of anti-inflammatory cytokines. Summary: Successful AIT establishes the reinstatement of immune tolerance toward allergens, reduces allergic symptoms, and improves clinical treatments in patients. B cells play a central role in this process through antibody-independent immune regulatory processes in addition to the production of IgE-blocking antibodies.